2013
DOI: 10.3141/2387-14
|View full text |Cite
|
Sign up to set email alerts
|

North America's First E-Bikeshare

Abstract: The integration of electric bicycles (e-bikes) with bikesharing could increase the utility of bikesharing through a reduction of some barriers to bicycling and an increase in the number of prospective users. North America's first e-bikesharing system (cycleUshare) at the University of Tennessee, Knoxville, offers a new, sustainable transportation option for students, faculty, and staff. The cycleUshare system with two stations was launched as a small pilot project to study the technology and its users' experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 8 publications
(6 reference statements)
0
44
0
6
Order By: Relevance
“…Again, they found that e-bike users tended to replace car trips, even among conventional bicyclists. Three small-sample studies [13,20,25] found that e-bike users do indeed use e-bikes for broader trip purposes than bicycles. Since those studies were published, the e-bike market has grown and become more mainstream, with major international manufacturers entering the market and conventional bicycle companies adopting an e-assist product line.…”
Section: North American E-bike Usersmentioning
confidence: 99%
See 1 more Smart Citation
“…Again, they found that e-bike users tended to replace car trips, even among conventional bicyclists. Three small-sample studies [13,20,25] found that e-bike users do indeed use e-bikes for broader trip purposes than bicycles. Since those studies were published, the e-bike market has grown and become more mainstream, with major international manufacturers entering the market and conventional bicycle companies adopting an e-assist product line.…”
Section: North American E-bike Usersmentioning
confidence: 99%
“…With power assistance, many barriers to cycling are reduced or overcome, including increasing age, physical limitations, hilly terrain, a lack of time, and a lack of fitness or the perception of fitness that is needed to cycle [1,13,14,[19][20][21][22]. While power assistance makes riding easier, riders still gain some physical activity benefits by pedaling.…”
Section: E-bikementioning
confidence: 99%
“…No entanto, as bicicletas elétricas do tipo pedelec praticamente eliminam esse problema, já que elas possuem um motor elétrico que auxilia a pessoa Langford et al (2013) analisaram o primeiro ano de uso do mesmo sistema.…”
Section: Introductionunclassified
“…While much of the emphasis in the past has been on electric automobiles, attention has recently been increasingly focused on electric bicycles, which have tremendous potential as a zero-point-source-emission solution for urban transportation [2,10,11]. E-bikes are rapidly gaining acceptance as a desirable and viable alternative, and there is increasing municipal and consumer readiness to invest in cycling in general and in e-bikes specifically [12][13][14].…”
Section: Related Workmentioning
confidence: 99%